Translation Surfaces in the 3-Dimensional Pseudo-Galilean Space Satisfying: \(\boldsymbol{\bigtriangleup^{II}\, r_i=λ_i r_i}\) - Ahmed, Azzi; Mohammed, Bekkar; Hanifi, Zoubir (Communications in Mathematics and Applications, 2021)
In this paper, we classify translation surfaces in a \(3\)-dimensional Pseudo-Galilean space \(\mathbb{G}_{3}^1\) under the condition \(\bigtriangleup^{\rm II}\, r_i=λ_i r_i\), where \(r_i\) are the components of the position vector, \(λ_i\in\mathbb{R}\), \((i=1,2,3)\), and \(\bigtriangleup^{\rm II}\) denotes the Laplace operator with respect to the second fundamental form.